Bersukacita Karena Penghakiman Allah: Sebuah Penelitian Puitis Mazmur 58 - Yasuo Thunderstorm Huang (Indonesian Journal of Theology, 2018)
Unjust judgment ever haunts human life. One instance of such injustice is recorded in Psalm 58. Injustice begets deep human suffering. This article puts forth a reading of Psalm 58 using poetic criticism in an attempt to disclose the psalmist’s feelings amid his suffering. Taking on this aspect of the psalmist’s feelings differs subtly from other scholarly approaches to reading Psalm 58, such as the contribution of Marvin E. Tate. Instead, here the psalmist’s feelings are disclosed in the very fact of the suffering he experiences, although suffering is not the inception of the psalmist’s feelings. The suffering he experiences creates nothing of his feelings. Rather, divine intervention amid suffering is what stirs the very feelings being wrought within the psalmist. That intervention is registered in the psalmist’s recognition toward God. In the end, the event of God’s just judgment might inspire the church’s own disposition against unjust judgment.